Capital Structures and Portfolio Composition During Banking Crisis : Lessons from Argentina 1995 - Ramos, Alberto (IMF Working Papers; Working Paper ;, 1998)
This paper constructs a theoretical framework that rationalizes banks' short- and long-run adjustment dynamics-in portfolio composition and in the capital structure-following a period of financial distress. The model captures stylized facts about banks' behavior following a shock to the capital base-namely, the rush to liquidity and credit crunch. Bank panel data show that Argentine domestic retail banks underwent a period of adjustment of six quarters following the Mexican devaluation crisis, reducing their risk-exposure since, owing to bank capital scarcity, depositors became less prone to tolerate bank default risk. Foreign-owned banks suffered a milder shock and adjusted immediately.